DAMPAK GAYA HIDUP KONSUMTIF PADA KEHIDUPAN SOSIAL DAN PRESTASI MAHASISWA - Wahidah, Rohmatul; Imran, Imran; Bahari, Yohanes (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The title of this research is The Impact of Comsumtive Life style on Student Social Life and Achievement residing in girl boarding house â€œSalsabilaâ€ at karangan street no. 21, Pontianak. The problem in this thesis was the impact of students consumptive lifestyle on social life and academic achievement. The general purpose of this study is the impact of the studentâ€™s lifestyle on social life and academic achievement. The approach used in this research is qualitative approach with descriptive method. The data collection techniques used were observation techniques, interview guides and documentation. The informants of this reseacrh were students who reside in salsabila boarding house and the owner of salsabila boarding house. From the results of research that has been done, the first sub-issue is how the impact of consumptive lifestyles on social life who lived in girl boarding house salsabila, located on karangan street, no 21 pontianak city, there were found a communities among the individual, especially students community that is based on different levels of different social classes. Â Â Â Â Â Â Â Â Â Keywords : consumtipve lifestyle, social life, Student achievemen